Improvement of reading comprehension through computer-assisted language learning in Iranian intermediate EFL students - Marzban, Amir (Procedia computer science, 2011)
The present study investigated the effect of ICT and more specifically CALL on the quality of students’ reading comprehension in an Iranian academic setting. For this study, a pre-test / post-test experimental design was developed. 30 students out of 60 subjects were randomly selected to form the treatment group and the rest of them formed the control group. One instructor taught reading comprehension to both groups using CALL and the other group was taught reading comprehension in the traditional way. The result of the study showed that there was a statistically significant difference at the level of P<0.05 between reading comprehension scores of the two groups; therefore, it was concluded that the use of computer assisted educational techniques can improve students’ reading comprehension.